INDUSTRI MOBIL NASIONAL : PERSPEKTIF BERLIAN PORTER - Elvy Maria Manurung (Center for Economic Studies Universitas Katolik Parahyangan, 2012)
Our national industry today does not have a basis yet for competitive advantage. Since the beginning of the aircraft industry (IPTN) decades ago up to the present, our country has not had yet the competitive advantage in one particular industry that can compete in a global trade. “Kiat Esemka” seems to encourage the emergence of national automobile industry. This also prove that our nation in this Creative Era (an era that emphasize creativity as a primary source) has the potential to compete with other countries. Although there is no prove yet as to whether we have the diamond in our country for competing successfully in automotive industry, or further to have the unique competitive advantage. However, the opportunity to have some competitive industries is open widely.Key words : national industry, competitive advantage.